The Effect of Financial Performance on Firm Value in Transportation Sector Companies Listed on the Indonesia Stock Exchange (IDX) During 2020–2024 - Amrulloh, Amri; Hartono, Halleina Rejeki Putri; Kurniawan, Yopie Diondy; Almasah, Nyimas Mahani (LPPM STIE Kasih Bangsa, 2025)
This study aims to analyze the effect of financial performance on firm value in transportation sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research uses a quantitative approach with a causal associative method, employing secondary data obtained from annual financial statements and capital market databases. Financial performance is measured using three indicators—Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE)—while firm value is measured using Earnings Per Share (EPS) and Price to Book Value (PBV). Data analysis is conducted using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (SmartPLS). The results show that financial performance has a positive and significant effect on firm value, as indicated by a path coefficient of 0.8622, a t-statistic of 31.2125, and a p-value of 0.000. These findings imply that the better a company’s financial performance, the higher its firm value. The results also support the Signaling Theory, which explains that strong financial performance serves as a positive signal to investors about a company’s future prospects. The study highlights the strategic importance of profitability improvement, cost efficiency, and transparency in financial reporting to enhance firm value and strengthen investor confidence, especially in the transportation sector that plays a crucial role in post-pandemic economic recovery.